THE EFFECT OF BRAND AWARENESS AND QUALITY PERCEPTIONS ON BRAND EQUITY OF KOFFIE MINOR SEMARANG - Nugroho, Jati; Supaya, Sandi; Ramadany, Rania Putri (Jurnal Akuntansi dan Bisnis, 2023)
This study aims to determine the effect of brand awareness and perceived quality on the brand equity of Koffie Minor Semarang. The research sample was 60 respondents who were selected using purposive sampling technique. Primary data collection using interviews and questionnaires, as well as literature study for secondary data. Instrument testing is done by testing the validity and reliability. Regression analysis used is multiple regression analysis consisting of t test, F test and coefficient of determination. The results of the coefficient (R2) show 0.773 this means that brand awareness and perceived quality have an effect of 73.3% on brand equity, while the remaining 26.7% is influenced by other variables not discussed in this study. Partially,